Climate ambitions for European aviation: Where can sustainable aviation fuels bring us?. (April 2023) - Mayeres, Inge; Proost, Stef; Delhaye, Eef; Novelli, Philippe; Conijn, Sjaak; Gómez-Jiménez, Inmaculada; Rivas-Brousse, Daniel
Abstract: This paper assesses the costs of policies to promote the uptake of sustainable aviation fuels to reduce the greenhouse gas emissions of aviation in the EU. Different policies for attaining a minimum sustainable aviation fuel share are assessed, taking into account sustainability requirements and the costs and potential of feedstock supply. The cost-effectiveness of these policies is compared to simpler CORSIA-type emission trading schemes, using a model that combines the demand functions for road, rail and maritime transport fuels, the supply functions of the related feedstocks as well as the environmental sustainability characteristics of the fuels. For aviation a distinction is made between fuel demand for intra-EU flights and for incoming and outbound EU flights. It is shown that policies that aim to achieve a minimum share of 3.5% or 5.25% sustainable aviation fuels by 2030 in the EU are 5–10 times more expensive to reduce greenhouse gas emissions than a simpler emission trading mechanism like CORSIA. Highlights: Imposing an uptake of sustainable aviation fuels in the EU is an expensive option. The cheapest policy alternatives rely on emission trading with other sectors. Supply problems quickly arise with tightened sustainability constraints.